ANALISIS MANAJEMEN RISIKO PROYEK PEMBANGUNAN JALAN AKSES BANDARA VVIP IKN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) PADA PT. ABC - Al Muzazin; Kartono Wibowo; Moh Faiqun Niam (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2026)
AbstractAt the road construction stage, it often faces various problems. Risk management applied to the IKN VVIP Airport Access Road Construction Project at PT. ABC is incomplete, so this study aims to identify potential risks, assess the level of risk, measure the impact of possible risks, and plan mitigation. In this study, the Failure Mode and Effect Analysis (FMEA) method is used to analyze risks, a risk matrix is used to evaluate risks, and a focus group discussion (FGD) with 8 respondents from PT ABC who have more than 5 years of working experience in project implementation is used to determine risk mitigation. The results of this study show that there are 35 risk variables, including 17 risks of road project work, 10 risks of remote areas, and 8 risks of national issues. After conducting a risk analysis, 13 risk variables were obtained that were considered critical, namely poor project time control, errors in the implementation method, errors in the initial drawing design, late ordering and delivery of materials, equipment damage, poor quality management procedures, less than optimal equipment productivity, evaluation of work specifications that were not carried out, considerable labor requirements, limited availability of natural materials, limited competent sub-contractors, lack of equipment to support project activities, limited communication technology (internet, cellular network), and improving the economy of the area around the new capital city. Of the 13 risk variables, six very high-risk categories and seven high-risk categories were found. Management mitigates the 13 risks by paying attention to work equipment and materials, checking work access, scheduling work plans, selecting subcontractors and workers, and improving the economy around the project.Keywords: Risk Analysis, Risk Mitigation, FMEA Method, IKN Project